Lissamine Green in Ophthalmology: A Comprehensive Review of Diagnostic and Clinical Applications - Stefano Barabino; Pasquale Aragona; Stefano Bonini; Emilia Cantera; Antonio Di Zazzo; Giuseppe Giannaccare; Andrea Leonardi; Giancarlo Montani; Alessandro Mularoni; Vincenzo Orfeo; Edoardo Villani; Fabrizio Zeri; et al. (Ophthalmology and Therapy)
Abstract Lissamine green (LG), a diagnostic dye that stains devitalized or damaged epithelial cells, is widely used to assess ocular surface integrity, enabling the detection of inflammation, epithelial defects, and conjunctival irregularities. To explore the diagnostic and clinical applications of LG in ophthalmology, focusing on its use for ocular surface diseases, a group of experts in ophthalmology and optometry participated in an advisory board to share their clinical practice experience with the use of LG. Building on the advisory board contents, this narrative review was based on a combination of expert opinions from the roundtable discussion and a comprehensive review of the current literature. This review highlights the clinical relevance of LG as a diagnostic tool in ocular surface disease and underscores the potential of newer formulations to enhance diagnostic accuracy. In particular, the review highlights the historical development of LG use in ophthalmology and its advantages over other dyes, especially in terms of patient comfort and safety, as well as specific clinical protocols for using LG in assessing dry eye disease severity and inflammatory responses. Additionally, the review examines recent advancements in LG formulations, which enhance their utility in clinical practice, and addresses safety considerations. Potential areas for future research are also discussed, particularly in developing standardized evaluation procedures using artificial intelligence.